(untitled) (Palíndromo, 2020)
Sophie Calle, in Purloined, exhibited absent works through descriptions made by museum employees; Jean-Paul Thenot, in Cent lectures de Marcel Duchamp, asked a hundred people what Duchamp’s works evoked in them. In order to capture the public’s perception of art in Porto Alegre, I reproduced the exercises of Calle and Thenot (with adaptations), having as object three works of the Ío duo of artists exhibited in 2018 at Santander Cultural. I applied questionnaires to one hundred visitors of the institution, asking them to describe each of the works in a word. I also conducted oral interviews with Santander Cultural employees, who were invited to describe the works. Content analysis of the collected data indicates that most answers do not correspond to the epistemological definition of “description”. This article proposes explanations for this result, such as the difficulties of the relation between image and word or the influence of traditional theories on the interpretation of art.